Christian sexual ethics in a time of HIV / AIDS - a challenge for public theology - Haspel, Michael (Verbum et Ecclesia, 2004)
HIV / AIDS poses an enormous challenge for the Christian church in Africa. Though many congregations engage in practical social programmes addressing the medical and social problems related to HIV / AIDS often there is no adequate theological concept dealing with HIV / AIDS. This article argues that starting from biblical insights and Christian anthropology in the current situation a contextual theology adressing HIV / AIDS and a respective sexual ethics have to be developped which enables Christians to live responsibly in a time of HIV / AIDS without demonising sexuality. This, in turn, could contribute to the ethical discourse in civil society and thus foster the development of a public theology.
Free